Tindakan Sosial dalam Cerpen “Fii Biladi al-Ajaib” Karya Kamil Kailani Berdasarkan Perspektif Max Weber - Fika Burhan Tajalla; Muhammad Farihul Qulub; Laily Fitriani (Uktub: Journal of Arabic Studies, 2022)
Social action that occurs in a person is a form of response to various motives of problems and problems that occur in society. Social action has a close relationship with social life, one of which is behavior and attitudes. The purpose of this study is to describe the analysis of social action in the short story "Fii Biladi al-Ajaib" by Kamil Kailani. This research method uses content analysis of the data in this study in the form of sentences containing social actions in the short story "Fii Biladi al-Ajaib". Data collection techniques used reading techniques and note-taking techniques. Data analysis techniques in this study are in the form of data reduction, data presentation, and conclusion. The results of this study indicate the theory of social action based on Max Weber in the short story "Fii Biladi al-Ajaib", including the discovery of (1) value rationality actions, in the form of making others happy, holding fast to a belief, and respecting the invitation of others, (2) effective action in the form of emotions, (3) acts of instrumental rationality in the form of preserving feelings and saving the future.